PROFIL BERPIKIR KRITIS SISWA KELAS VII SMP DALAM MEMECAHKAN MASALAH PADA MATERI BANGUN DATAR SEGITIGA - Wayan Mega Setiawan; Sukayasa; I Nyoman Murdiana (Jurnal Elektronik Pendidikan Matematika Tadulako, 2022)
This study aimed to obtain a description of the critical thinking of students in class VII SMP in solving problems on the material of build flat triangle. This type of research is descriptive-qualitative with a case study approach. In this study, three students were selected, each of whom had high, medium and low mathematical abilities. Data collection techniques in this study by providing questions about the triangle material and interviews. The triangle material was chosen because it can trigger students to use their higher-order thinking skills. The results of this study indicate that the critical thinking profile of students in class VII of SMP Negeri 1 Mepanga in solving problems on the material of build flat triangle is as follows, the critical thinking profile of students with high mathematical abilities (PM) includes, providing simple explanations, building basic skills, solving skills problem and conclude, the critical thinking profile of students with moderate mathematical ability (SR) includes, providing simple explanations, problem solving and concluding abilities and the critical thinking profile of students with low mathematical ability (AL) only provides a simple explanation.